Evaluation of Uses and Gratifications on Online Otome Games - Vanya Nouvanty; Tri Lathif Mardi Suryanto; Asif Faroqi (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2023)
In this advanced world of technology, games have become a fun entertainment that is loved by the people. This study aimed examine online otome game, which in this case study is Tears of Themis, using uses and gratification theory-based model that consists of enjoyment, fantasy, escapism, social interaction, social presence, achievement, self-presentation and also age moderation variable which affects the continuance intention to play Tears of Themis. The analysis testing and model development were performed using PLS-SEM method on 135 respondents who were Tears of Themis players from Indonesia. The results revealed that enjoyment and achievement have significantly affected the continuance intention of playing Tears of Themis. Meanwhile, the moderation test results showed no relation between all independent variables and continuance intention. But based on the age sub-groups, 16 — 19 years old subgroup are affected by enjoyment and self — presentation on Tears of Themis continuance intention and 20 — 24 years old subgroup are influenced by enjoyment on Tears of Themis continuance intention. These results can be used as insight for development of online otome games to improve the quality of games in the future.